2021
DOI: 10.15537/smj.2021.42.3.20200695
|View full text |Cite
|
Sign up to set email alerts
|

Does the fibrinogen/albumin ratio predict the prognosis of pregnancies with abortus imminens?

Abstract: To investigate the fibrinogen/albumin ratio (FAR) of pregnant women with abortus imminens (AI) and its prognostic value for predicting spontaneous abortion. Methods: A total 102 early pregnancies, 52 had been diagnosed with AI and 50 ages and body mass index matched healthy control pregnant women were included in this prospective observational study conducted in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Recently, research on FAR in pregnant women and its association with obstetric complications has increased. In a study conducted on pregnant women with threatened miscarriage, it was reported that abortion was more common in the group with high FAR levels [32]. Another study conducted by Hrubaru et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research on FAR in pregnant women and its association with obstetric complications has increased. In a study conducted on pregnant women with threatened miscarriage, it was reported that abortion was more common in the group with high FAR levels [32]. Another study conducted by Hrubaru et al.…”
Section: Discussionmentioning
confidence: 99%
“…FAR is a ratio of fibrinogen and albumin, which is generated at no extra cost when biochemistry and coagulation function tests are performed in routine antenatal examinations. Multiple studies have suggested that elevated levels of FAR are associated with many diseases, such as abortus imminent, [ 16 ] systemic lupus erythematosus, [ 17 ] acute coronary syndrome, [ 24 ] rheumatoid arthritis [ 25 ] and ankylosing spondylitis, [ 26 ] which are associated with an inflammatory state. Hence, it has been concluded that FAR may be a better indicator for many systemic inflammation diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 ] Since preeclampsia is also associated with some degree of inflammatory burden, [ 4 ] it is reasonable to study other inflammatory markers in preeclampsia. In addition, fibrinogen to albumin ratio (FAR) is a new inflammatory marker and has been proven to have excellent predictive value for abortus imminent, [ 16 ] systemic lupus erythematosus, [ 17 ] and ascending aortic aneurysm. [ 18 ] However, there has been no reliable research on whether FAR can predict PE or evaluate its severity.…”
Section: Introductionmentioning
confidence: 99%
“…Studi sebelumnya telah menyarankan bahwa invasi sitotrofoblas yang memadai ke dalam lapisan endometrium dan miometrium dan transformasi mereka yang cukup menjadi arteri spiral pada trimester pertama kehamilan adalah batu utama untuk perkembangan embrionik yang sehat (Usta et al, 2021).…”
Section: Pendahuluanunclassified